IMPLEMENTATION OF PROJECT BASED LEARNING MODEL BASED ON CODING SCRATCH PRODUCTS TO INCREASE STUDENTS' UNDERSTANDING OF PRESERVING NATIONAL CULTURE - Siswandi, Rudi; Mahanani, Dila; Salahudin, Muhammad; Isnaini, Isnaini; Budiarsani, Ni Luh; Hafsah, Hafsah (Abjadia : International Journal of Education, 2024)
Study This was carried out in order to find out what kind of impact and influence it had on increasing students' understanding of cultural preservation and advancing national culture through learning with a Science, Technology, Engineering, and Mathematics (STEM) Project Based Learning (PjBL) model based on Scratch coding products. This research method is a qualitative approach with the type of classroom action research. The subjects or data sources for this research were Pancasila education teachers, and class VIII A students at SMPN 1 Labuapi, and to strengthen the research results, informants were determined or acted as learning reviewers who had an understanding related to the learning being carried out. The informants or reviewers for this research were determined with special considerations, were not haphazard, and could be accounted for. Data collection was carried out using observation techniques (diagnostic assessment), questionnaires (to measure student achievement), interviews, and documentation. Data analysis was carried out using the Kemmis McTaggart model which took place in four cycles, namely Planning, Implementation, Observation and reflection. This research shows that learning using the PjBL model STEM approach based on coding scratch products has a significant impact significant In increasing students' understanding regarding the preservation and advancement of national culture which is able to provide a better learning experience, systematic understanding and 21st century abilities, it can also be seen from the high level of enthusiasm and motivation for students to learn.